2011
DOI: 10.2147/ijn.s18267
|View full text |Cite
|
Sign up to set email alerts
|

High-energy ball milling technique for ZnO nanoparticles as antibacterial material

Abstract: Nanoparticles of zinc oxide (ZnO) are increasingly recognized for their utility in biological applications. In this study, the high-energy ball milling (HEBM) technique was used to produce nanoparticles of ZnO from its microcrystalline powder. Four samples were ball milled for 2, 10, 20, and 50 hours, respectively. The structural and optical modifications induced in the ‘as synthesized’ nanomaterials were determined by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(130 citation statements)
references
References 45 publications
6
107
2
Order By: Relevance
“…In other words, a balance between the striking force causing friction on the particles, and the material resistance, is achieved at a particle size of around 20 nm. Similar results on obtaining ultrafine, well-shaped nanoparticles were also reported earlier [31].…”
Section: Methodssupporting
confidence: 89%
“…In other words, a balance between the striking force causing friction on the particles, and the material resistance, is achieved at a particle size of around 20 nm. Similar results on obtaining ultrafine, well-shaped nanoparticles were also reported earlier [31].…”
Section: Methodssupporting
confidence: 89%
“…22 Furthermore, previous studies have shown that the smaller the ZnO particle size, the greater the efficacy in inhibiting the growth of bacteria, involving both the production of reactive oxygen species and the accumulation of nanoparticles. 7,10,23 However, nanoparticles of ZnO were previously reported to act both as bactericidal agents 24 and bacteriostatic agents, 25 perhaps thereby limiting their biomedical use.…”
Section: Morphological Analysismentioning
confidence: 99%
“…ZnO nanostructures have vast applications such as dye sensitized solar cells, field effect transistors, targeted drug delivery, anticancer agents, and antibacterial activity. [4][5][6][7][8] Recently, it has been reported that the doping of ZnO nanostructures with other elements can enhance its various properties. 9 Commonly, different elements as a dopant in ZnO can be categorized into two groups: one group can substitute for zinc (Zn) and the second group for oxygen (O).…”
Section: Introductionmentioning
confidence: 99%